John Hancock Douglas papers - Douglas, John Hancock, 1824-1892.
Letters (1861-1864) from Douglas to his brother, George Douglas, written from various headquarters of the U.S. Sanitary Commission, of which Douglas was chief of inspection and associate secretary. Manuscripts and printed copies of his writings, and pencilled notes (1885) from Ulysses S. Grant to Douglas, who was his physician. Includes typescript of "Record of the Last Days of the Magnanimous Soldier, U. S. Grant" by Douglas, a scrapbook, engravings, and other papers relating to Grant.
Physician.
Collection material in English.
Keywords: Douglas, George, -- active 1861-1864 -- Correspondence; Grant, Ulysses S. -- 1822-1885.; United States Sanitary Commission; Medicine -- Practice -- New York (State) -- New York; United States -- History -- Civil War, 1861-1865 -- Medical care; Physicians